"Everything Happens in the Hallways": Exploring User Activity in the Corridors at Two Rehabilitation Units. (April 2018) - Colley, Jacinta; Zeeman, Heidi; Kendall, Elizabeth
Objectives: This research aimed to examine the role of the corridors in specialist inpatient rehabilitation units to inform future design of these spaces. Background: In healthcare settings, such as rehabilitation units, corridors have often been designed simply as spaces allowing movement between other locations. However, research suggests that corridors may be places where important social and care-related activities take place. How corridors are used and understood by patients and staff in inpatient rehabilitation settings is unclear, and a greater understanding of the role of corridors in these settings could help to inform more supportive design of these spaces. Methods: Independent observations of user activity were conducted at a major metropolitan inpatient spinal injury unit (SIU) and brain injury unit (BIU). Interviews were conducted with SIU patients ( n = 12), and focus groups were conducted with SIU staff ( n = 23), BIU patients ( n = 12), and BIU staff ( n = 10). Results: Results from the observations showed that the corridors were used frequently across the day, particularly by staff. Thematic analysis of staff and patient experiences found three key themes describing how corridors were used: (1) moving around, (2) delivery and experiences of quality care, and (3) a "spillover space." Conclusions: Results demonstrate that corridors not only have an important role as connective spaces but are also used as flexible, multipurpose spaces for delivery of quality care and patient experiences. Future design should consider how these spaces can more deliberately support and contribute to patient and staff experiences of rehabilitation.